HUBUNGAN ANTARA PERILAKU MEROKOK DAN PENYAKIT JANTUNG KORONER DI UNIT RAWAT INAP RUMAH SAKIT UMUM SANTO ANTONIUS PONTIANAK TAHUN 2012 - ., Kevin (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2015)
Background: Coronary heart disease and itâ€™s complication was one of themost cause of death worldwide. Smoking was one of the risk factors ofcoronary heart disease. The objective of ths study was to examine therelationship between cigarette and coronary heart disease in SaintAntonius Hospital. Methods: This research was analytic study with casecontrol approach. One hundred and thirty participants were recruited usinga non-probability sampling (consecutive sampling) technique.Measurement was taken include subjectâ€™s based on AHA (american heartassociation) diagnostic criteria for myocardial infarction and anginapectoris with a confirmation of an internist or a cardiologist, cigarettesmoking status based on NSDUH (National Survey on Drug use andHealth). Based on cigarette smoking status, all participants were dividedinto two groups that has been smoking and never smoke. Based ondiagnostic criteria, all participants were divided into two groups that wassubjects conary heart disease and subjects with coronary heart disease.Data were analyzed with Statistical Product and Service Solution Program(SPSS). Results: There was statistically significant relationship (P <0,002) betweeen cigarette smoking and coronary heart disease. Therelative risk (odds ratio [OR] and 95% conï¬dence interval [CI]) ofdeveloping coronary heart disease among the cigarette smoking subjectswas (OR 3,23; CI 1,52 â€“ 6,87). Conclusions: There is signicantrelationship between cigarette smoking and coronary heart disease.Cigarette smoking is the risk factor of coronary heart disease andincreased the risk of developing coronary heart disease among thecigarette smoking subjects is 3,23 fold compared with the normal weightsubjects.Key words: coronary heart disease, cigarette smoking, saint antoniusgeneral hospital pontianak